'The wardrobe diet': teaching sustainable consumption through experience with undergraduates in the USA. Issue 3 (2nd September 2019) - Rhee, Jongeun; Johnson, Kim K. P.
ABSTRACT: Fast fashion retailers provide consumers with low quality, inexpensive, and trendy clothing. Fast fashion items are attractive to young consumers who have limited budgets yet want to be in trend. The combination of increased fashion purchasing with the short lifespan of items can have harmful environmental impacts tied to both production and disposal. Researchers noted a behavioural gap between attitudes toward sustainability and behaviours. Consumers who indicated that socially responsible consumption was important to them, their attitudes did not carry over to influence their actual purchasing behaviours. Our goal was to implement a learning experience that enabled students to recognise their clothing consumption practices and identify how sustainability could be positively impacted by altering their individual consumption behaviours. An experience-based learning activity titled 'the wardrobe diet' was assigned to undergraduates. The wardrobe diet required students to identify and wear a total of six clothing items for 30 days. Evidence that the wardrobe-diet was a successful learning experience came from students reports that indicated they had already begun to alter their consumption.